To boost your overall performance, you should focus on the crucial bike-run transition - Anderson, O. (Peak Performance, 2001)
It is discussed why the bike-run transition is such a critical period and that it has to be trained with special focus. You have to take into concern that transition-phase running is harder, drafting reduces physiological stress, the 'death-march' style after quitting the bike, working out blindfold might help and cycling power.